Impact of analytic conventions on outcome measures in two longitudinal studies of dental caries - SKEET, Muriel (Blackwell Synergy, 2000)
Caries increment is the primary outcome measure used in most longitudinal studies of caries. Its computation requires the adoption of specific analytic conventions for handling examiner misclassification (‘‘reversals’’), teeth lost due to caries, and multiple events such as caries initiation and progression. However, little is known about the impact of these analytic conventions on cumulative incidence and incidence density – two additional outcome measures used in longitudinal studies.